International Economic Cooperation of Central Asian Countries on Energy Efficiency and Use of Renewable Energy Sources - Kaliakparova, Gulnar Shaimardanovna; Gridneva, YÐµlena Evgenevna; Assanova, Sara Sarsebekovna; Sauranbay, Sandugash Babagalikyzy; Saparbayev, Abdizhapar Djumanovich (International Journal of Energy Economics and Policy, 2020)
The purpose of this study is to identify priority areas for international cooperation of Central Asian countries to realize the potential of renewable energy sources and increase the efficiency of energy systems. Such scientific methods as literature analysis, comparative analysis, retrospective analysis, as well as the expert assessment method have been used in the study. The results of the study show that the countries of Central Asia have significant potential for the development of renewable energy. In recent years, interest in energy efficiency measures in Central Asia has been growing. Kazakhstan, Uzbekistan, and Turkmenistan consider renewable energy as a way to increase their oil and gas exports, while Tajikistan and Kyrgyzstan hope to reduce their dependence on energy imports from neighboring countries. At the same time, despite the enormous potential of renewable energy sources (RES), the actual deployment of renewable energy in the region remains low. The transition of the Central Asian countries' energy sector to new forms of energy production with a focus on renewable energy should be carried out in cooperation with countries with the best practices in the field of RES development. International cooperation will support the Central Asian countries in realizing their huge potential for RES and accelerating their pace of transition to renewable energy. Keywords: renewable energy, cooperation, energy resources, program, project. JEL Classifications: Q42, Q43, Q48, O19, R19, F59. DOI: https://doi.org/10.32479/ijeep.9962